Diseño de interiores : locales comerciales (The Architectural Review, 1996)
Pawson, John. Shop, Bond Street, London / Bentheim, David. Shop, West London / Nouvel, Jean. Shop, Berlin Germany / Din Associates. Shop, Covent Garden, London